(untitled) (Revista Direito em Debate, 2024)
This text analyzes the relationship of trust between citizens and the State, discussing how this bond is formed and which instruments of popular participation in power demonstrate a greater or lesser influence exercised by the people in state decision-making. The research problem that guides the investigation can be summarized as follows: under what conditions can the relationship of trust between citizens and the State be enhanced/reinforced through the use of instruments of popular participation based on new technologies in decision-making? The general objective of the text is to evaluate to what extent new technologies can contribute to intensifying citizen trust in the State through mechanisms of e-Government, e-Governance and e-Democracy. To achieve the general objective, the specific objectives outlined, which correspond to the structure of the article, are: a) to analyze the intensity of relationships of trust between citizens and the State in contemporary times, revisiting contractualist theories to think about today’s society in the search for an understanding of the new mechanisms of the exercise of power; b) assess to what extent the bond that keeps the people and their representatives united in a relationship of mutual trust can be strengthened by improving the instruments for the population’s participation in power, using new technologies; c) measure the influence exerted by the people in the State’s decision-making, especially through the use of e-Government, e-Governance and e-Democracy mechanisms, investigating whether this participation strengthens the bond of trust of the citizens in the State entity. The research was conducted using the hypothetical-deductive method, using bibliographic and documentary techniques. As a result, the text points to the finding that the bonds of trust of the citizens in the State tend to be strengthened as new technologies propose greater proximity of the people in the decision-making processes.